2020
DOI: 10.1111/1750-3841.15314
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fraud in high‐quality rice by near‐infrared spectroscopy

Abstract: A key feature of food fraud is the use of a lower value ingredient to imitate an authentic product. This study was based on near‐infrared spectroscopy (NIRS) analysis technology, partial least squares discriminant analysis (PLS‐DA), and a support vector machine (SVM) to detect whether high‐quality rice was mixed with other varieties of rice. As an aid to qualitative discrimination, PLS was used to establish the quantitative analysis model to assist in the recognition of the degree of fraud. Due to the direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…NIR analysis technology, PLS-DA, and SVM have been used to detect whether highquality rice was mixed with other varieties of rice. NIR spectral data analyzed using PLS-DA and a SVM algorithm, was shown to be a feasible method (5% detection limit) for the rapid identification of fraudulent rice varieties blended with authentic Wuchang rice samples [133].…”
Section: Nir Spectroscopy In Rice Authenticationmentioning
confidence: 99%
See 1 more Smart Citation
“…NIR analysis technology, PLS-DA, and SVM have been used to detect whether highquality rice was mixed with other varieties of rice. NIR spectral data analyzed using PLS-DA and a SVM algorithm, was shown to be a feasible method (5% detection limit) for the rapid identification of fraudulent rice varieties blended with authentic Wuchang rice samples [133].…”
Section: Nir Spectroscopy In Rice Authenticationmentioning
confidence: 99%
“…Studies performed by Liu et al showed that those techniques represent a significant support to qualitative discrimination [133]. PLS was used to establish the quantitative analysis model to support in the recognition of the degree of fraud.…”
Section: Nir Spectroscopy In Rice Authenticationmentioning
confidence: 99%
“…In contrast, FTIR and NIR techniques are rapid, cost-effective, do not require specialized laboratory facilities and could therefore be used for pre-screening samples for SITE confirmatory or orthogonal analysis in enforcement work. Although FTIR and NIR spectroscopy were applied in several recent studies for the authentication of rice [27][28][29][30][31]33], to our knowledge, there have been no studies published that applied and compared benchtop FTIR-ATR and handheld NIR spectroscopy for differentiating the geographical origins of Thai Hom Mali rice.…”
Section: The Potential Of Ftir and Nir Spectroscopy Techniques For Geographical Differentiation Of Thai Hom Mali Ricementioning
confidence: 99%
“…The PLS-DA approach provided satisfactory results with total classification rates of 82.6% and 82.4% for authentic and adulterated samples, respectively. NIR spectroscopy was also reported as successfully discriminating authentic (n = 20) and adulterated (n = 140) rice from China [29]. Sampaio, Castanho, Almeida, Oliveira and Brites [30] applied NIR spectroscopy with principal component analysis (PCA), PLS-DA and support vector machines (SVM) for the discrimination and classification of rice varieties (Indica and Japonica) grown in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…Food fraud remains a significant problem for food regulators, importers, merchants, law enforcement personnel, and the consumer. NIR spectral data analyzed using partial least squares discriminant analysis and implementing a support vector machine algorithm, was recently shown to be a feasible method for the rapid identification of fraudulent rice varieties (5% detection limit) blended with authentic Wuchang rice samples [90]. The authors further noted that more uniform particle sizes aided in quantitative analysis (i.e., 100 mesh > 70 mesh > 40 mesh > full granules).…”
Section: Grains and Floursmentioning
confidence: 99%